Video Games and Outdoor Physical Activity for the Elderly: Applications of the HybridPLAY Technology - Clara Boj; Diego J. Díaz; Cristina Portalés; Sergio Casas (Applied Sciences, 2018)
The incorporation of the elderly into digital leisure has been especially driven by the development of games and applications that link the experience of play with beneficial effects for the user. Some of these benefits arise at a cognitive level, fostering intellectual activity of adults through playful experiences that combine audio-visual entertainment with brain training. Seniors are also engaged by active video games that use control interfaces to perform physical actions or activities, encouraging motor play. In this paper, we present the application of HybridPLAY for the elderly, a self-developed technology initially thought to transform playgrounds into scenarios for a set of interactive digital games. In this paper, we show that, although HybridPLAY was initially developed for children and teenagers, the versatile features of this technology make it appropriate also for the elderly. After having tested HybridPLAY with a small group of seniors who completed a usability test and a satisfaction questionnaire, we show that it is possible to combine playful entertainment with physical and mental activities in outdoor environments for the elderly.